1999
DOI: 10.1037/0022-006x.67.6.826
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing interactions between anxious mothers and their children.

Abstract: The present study assessed interactions between anxious mothers and their children, using observational techniques to elucidate potential mechanisms of anxiety transmission. Results revealed that anxious mothers were less warm and positive in their interactions with their children, less granting of autonomy, and more critical and catastrophizing in comparison with normal control mothers. Maternal anxiety status appeared to be the primary predictor of maternal warmth during interactions. Child anxiety status wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
337
5
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(384 citation statements)
references
References 39 publications
(57 reference statements)
37
337
5
5
Order By: Relevance
“…Furthermore, there were more conflicts during the interaction in the panic group than in the control group and the interaction outcome was more often controlled by mothers compared to the control group. These findings are consistent with the results of other top-down studies that found differences in parenting behaviors and expressed emotion between anxious and non-anxious parents (Hirshfeld et al 1997;Lindhout et al 2006;Whaley et al 1999) and concordant with the results of a recent meta-analysis (McLeod et al 2007) emphasizing the importance of parental control in the development and maintenance of anxiety disorders. No differences in interaction style were found whether a potentially threatening (hospital template) or non-threatening (house template) stimuli was used.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, there were more conflicts during the interaction in the panic group than in the control group and the interaction outcome was more often controlled by mothers compared to the control group. These findings are consistent with the results of other top-down studies that found differences in parenting behaviors and expressed emotion between anxious and non-anxious parents (Hirshfeld et al 1997;Lindhout et al 2006;Whaley et al 1999) and concordant with the results of a recent meta-analysis (McLeod et al 2007) emphasizing the importance of parental control in the development and maintenance of anxiety disorders. No differences in interaction style were found whether a potentially threatening (hospital template) or non-threatening (house template) stimuli was used.…”
supporting
confidence: 82%
“…requiring parent and child to work together in order to succeed), found that among anxious parents, lower level of granting of autonomy and higher levels of criticism in 1 st grade were significantly related to higher anxiety symptoms 6 years later. Interestingly, cross-sectional analyses did not indicate any group differences between anxious and non-anxious parents on any of the parenting behaviors.Further evidence of the important role of parenting in the etiology of anxiety disorders is derived from studies on children with anxiety disorder (Rapee 1997;Moore et al 2004;Whaley et al 1999). However, they assessed the relationship between parenting behaviors and child anxiety, without taking into account the anxiety status of the parents.…”
mentioning
confidence: 99%
“…These results typically show that greater childhood anxiety is associated with higher levels of perceived parental control and rejection (Rapee, 1997). Parents of anxious children were more likely to support avoidant strategies and least likely to encourage autonomy in order to protect their children from distress (Dadds, Barrett, Rapee, & Ryan, 1996;Whaley, Pinto, & Sigman, 1999). During problem-solving tasks, mothers of anxious children exhibited more involved, intrusive, and negative behaviors compared to mothers of nonanxious children (Hudson & Rapee, 2001).…”
Section: Relations Between Childhood Anxiety and Family Functioningmentioning
confidence: 99%
“…Genetic factors appear to play only a modest (but nevertheless significant) role in the familial transmission of SAD. Some researchers suggest that family environment might be even more predictive for offsprings" mental health than parental diagnostic status [111].…”
Section: Natural Course: Age Of Onset Duration Remission and Pattermentioning
confidence: 99%
“…Findings are often interpreted in terms of social learning mechanisms [83], such as parental modelling of anxious or avoidance behaviour [25,75,76], or parental attitudes and actions [14,111] by which parents actively manage the child"s behaviour [e.g., 77].…”
Section: Natural Course: Age Of Onset Duration Remission and Pattermentioning
confidence: 99%